KOMITMEN KEAGAMAAN KOMUNITAS MUSLIM TIONGHOA: STUDI KASUS PADA LEMBAGA PERSATUAN ISLAM TIONGHOA INDONESIA KOTA SURABAYA - Fahrur Rozi (Tarbawi, 2023)
This study aims to explore the religious cases in PITI Surabaya from two different perspectives related to religious motives. According to the perspective of the facilitator, the majority of the Chinese Muslim community enter and learn Islam because of marriage and personal interests, while the perspective of the congregation shows that they embrace Islam out of self-awareness and repentance. The researcher uses the religious of commitment theory approach through five dimensions to formulate research problems and uses qualitative research methods with an intrinsic case study approach. The results of the study show that the Chinese Muslim community has a deep understanding of religion in terms of doctrine and textual, applying their religious understanding by actively attending mentoring classes, and having a high religious commitment with the effect of changes in their behavior and participation in religious activities at the PITI institution. In addition, the study also examines the religious contributions of the Chinese Muslim community to the surrounding community and the impact of the changes they experience after embracing Islam.